The Efficacy and Safety of the mTOR Signaling Pathway Activator, MHY1485, for in vitro Activation of Human Ovarian Tissue - Wu, Shuang; Wang, Yining; Ding, Haixiang; Sun, Ningxia; Liu, Yan; Wang, Liang; Sheng, Fei; Zhang, Honghong; Yang, Fu; Li, Wen (Frontiers in Genetics, 2021)
(1) Background: Premature ovarian insufficiency (POI) is characterized by abnormal ovarian function before the age of 40. POI showed that primordial follicles developed in disorder. mTOR signaling plays a vital role in the process of follicle development. It has been verified that mTOR signaling pathway activator MHY1485 can promoted primordial follicle development in mice. We considered that MHY1485 would be a promising fertility preservation method for POI patients; (2) Methods: The fragmented ovarian tissues of normal woman cultured with activator MHY1485 in vitro, and then transplanted the control and activated ovaries into the kidney capsules of ovariectomized mice. Furthermore, we used the Infinium Human Methylation EPIC BeadChip to verify the DNA methylation level of ovarian tissues, thus exploring the effectiveness of them; (3) Results: MHY1485 stimulated mTOR, S6K1 and rpS6 phosphorylation. Cultured with MHY1485, ovarian weights were increased and endocrine function were restored. The number of growing follicles was increased. The in vitro activation process did not induce histological changes or abnormal DNA methylation occurance; (4) Conclusions: MHY1485 for in vitro activation (IVA) is effective for ovarian rejuvenation and is a potential therapeutic treatment for POI patients.